2014
DOI: 10.1016/j.matdes.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the mechanical and thermal characteristics of open cell aluminum foams by the electrodeposition of Cu

Abstract: Recently aluminum foaming has been of much interest due to its characteristics properties of light weight structure. Metallic foams are highly porous materials which present complex structure of three-dimensional open cells. This aspect causes strong limitations in mass transport due to electro-deposition technology. In this work, the electro-deposition of copper on aluminum open-cell foams substrates was developed, in order to enhance the thermal and mechanical properties of these cellular materials. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…Since the density of the produced samples is almost the same (around 513.5 kg/m 3 , after the third phase), they show quite similar values for yield strength and deformation energy. As it can be seen from previous works [2,3], the yield strength of third phase specimen enhances up to 232% in comparison to base aluminum foam. To demonstrate the effects of graphene electrodeposition on aluminum foam mechanical strength, two samples were chosen with very similar starting weight and density, such as 211 kg/m 3 and 2.4 g. During electrodeposition, both samples were treated to obtain almost identical weight percentage change (DP%) in all phases.…”
Section: Mechanical Propertiessupporting
confidence: 56%
See 3 more Smart Citations
“…Since the density of the produced samples is almost the same (around 513.5 kg/m 3 , after the third phase), they show quite similar values for yield strength and deformation energy. As it can be seen from previous works [2,3], the yield strength of third phase specimen enhances up to 232% in comparison to base aluminum foam. To demonstrate the effects of graphene electrodeposition on aluminum foam mechanical strength, two samples were chosen with very similar starting weight and density, such as 211 kg/m 3 and 2.4 g. During electrodeposition, both samples were treated to obtain almost identical weight percentage change (DP%) in all phases.…”
Section: Mechanical Propertiessupporting
confidence: 56%
“…As demonstrated by previous researches [2], there is a tight connection between the resistance of the foam and its density. Compression test results show that more the foam is dense and more it is resistant.…”
Section: Mechanical Propertiesmentioning
confidence: 64%
See 2 more Smart Citations
“…A copper coating aluminum open-cell foam was studied for enhancing thermal and mechanical properties by Antenucci et al [7]. They have reported that energy deformation behavior of the foam specimens was proportional to density.…”
Section: Introductionmentioning
confidence: 99%